Pengaruh Teknologi dalam Pendidikan Islam - Febrian Afriadi; Muhammad Fatih Hidayah; Gusmaneli Gusmaneli (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the influence of technology on Islamic education using a library research approach. The background of this study lies in the increasing use of digital technology in Islamic learning processes, both in formal and non-formal education. Technology is considered capable of expanding access to information, improving learning effectiveness, and supporting more interactive teaching methods. However, the integration of technology into Islamic education also presents challenges, especially in preserving Islamic values and student morality. The findings show that technology can serve as an effective medium for da'wah and education when used wisely and in accordance with sharia principles. Recommendations are addressed to educators and institutions to develop digital-based curricula that remain grounded in Islamic values.